Factors associated with suicidal ideation among older people in medical outpatient clinic - Syed Elias, Sharifah Munirah; Makhtar, Aniawanis; Ahmad Tarmidi, Nor Hazwani (Elsevier, 2021)
This study aimed to determine the prevalence of suicidal ideation and the associated factors with suicidal ideation among older people. This was a cross-sectional study. The present study was carried out from March 2018 to May 2018. In total, 200 older people aged 60 years and over were recruited from a medical outpatient clinic in Malaysia. The older people completed a self-administered questionnaire on sociodemographic background, depression, and suicidal ideation. The data analysis involved descriptive and inferential analysis using IBM SPSS Statistics version 23.0. The prevalence rate of suicidal ideation was 3%. There were significant associations between ethnicity (p < 0.00), marital status (p = 0.008), depression (p < 0.00) and suicidal ideation. Risk factors for suicidal ideation in older people are ethnicity, marital status, and depression. Future studies should focus on these factors in any intervention aimed to reduce suicidal ideation among older people in Malaysia.